Distribution features of lymphocytes with peanut agglutinin positive receptors in gums epithelium of rats in norm and after intrauterine antigenic action - Burega Yu. (Морфологія, 2015)
Background. According to the conception “Lymphocyte is the main factor of morphogenesis” changes in lymphocyte receptor repertory, induced by antigenic action in the fetal period of development, influence on organs and tissues development after birth. Functional activity of immunological immature PNA+ lymphocytes inducing the change in functioning, imbalance in formation cells of microenvironment, synthesis of intracellular substance and the fibers of extracellular matrix leads to violation of morphological and functional condition of organs. Objective. Determine the features of distribution of lymphocytes with receptors to peanut agglutinin in gingival epithelium of rats in norm and after intrauterine antigenic action. Methods. The object of the research was: 224 jaws of 112 white laboratory rats. The rats divided into three groups. First group – intact rats. Second group –rats, which were introduced 0,05 ml solution of antigen in the amniotic fluid on the 18th day of pregnancy by the method of N. Voloshyn, the third group – control, the animals were introduced intrauterine 0,05 ml of physiological solution on the 18th day of pregnancy. The antigen was split vaccine Vaxigrip 2009. Results and conclusion. In newborn animals, after intrauterine antigen action it was determined significantly increased content of PNA+ lymphocytes in the epithelium of gingival mucous, compared with control group, where PNA+ lymphocytes number gradually decreases. On the 11 th day of life, in animals of second group, quantity of intraepithelial PNA+ lymphocytes remains higher. On 45th day of postnatal formation its share does not significantly differ from similar indicators in all groups and decreases compared with neonatal period. Citation: Burega Yu. Distribution features of lymphocytes with peanut agglutinin positive receptors in gums epithelium of rats in norm and after intrauterine antigenic action. Morphologia. 2015;9(3):8-11.